The Effect of Implicit Followership Antecedents on the New Generation of Individuals - Lu, Kunxiu; Zhang, Wei; Zhang, Xiaoyan; Feng, Junshu; Li, Ying (Frontiers in Psychology, 2022)
This study used the Predisposition Proposition Theory of implicit followership to determine the effect of a proactive personality and core self-evaluation on the implicit followership of different schemas. Intertemporal survey data for one month from 452 university graduates were collected to evaluate that core self-evaluation significantly and positively affects positive implicit followership and significantly and negatively affects negative followership. However, the effect of proactive personality on implicit followership is not significant. The results of data analysis support the interpretation of propensity propositions in the study of personality traits. This study also determines the theoretical significance and practical application value.